Initial development of perpetrator confrontation using deepfake technology in victims with sexual violence-related PTSD and moral injury - Van Minnen, Agnes; ter Heide, Jackie June; Koolstra, Tilly; de Jongh, Ad; Karaoglu, Sezer; Gevers, Theo (Frontiers in Psychiatry, 2022)
Background Interventions aimed at easing negative moral emotions and restoring social bonds – such as amend-making and forgiving - have a prominent role in the treatment of moral injury. As real-life contact between persons involved in prior morally injurious situations is not always possible or desirable, virtual reality may offer opportunities for such interventions in a safe and focused way. Objective To explore pilot the effects of the use of deepfake technology in the treatment of moral injury related PTSD due to being forced by persons in authority to undergo and commit sexual violence (so-called betrayal trauma). Methods Two women who had experienced sexual violence underwent one session of confrontation with the perpetrator using deepfake technology. The women could talk via ZOOM with the perpetrator, whose picture was converted in moving images using deepfake technology. A therapist answered the questions of the women in the role of the perpetrator. Outcome measures were positive and negative emotions, dominance in relation to perpetrator, self-blame, self-forgiveness, and PTSD-symptom severity. Results Both participants were positive about the intervention. Although they knew it was fake, the deepfaked perpetrator seemed very real to them. They both reported more positive and less negative emotions, dominance in relation to the perpetrator and self-forgiveness, and less self-blame and PTSD-symptoms after the intervention. Conclusion Victim-perpetrator confrontation using deepfake technology is a promising intervention to influence moral injury-related symptoms in victims of sexual violence. Deepfake technology may also show promise in simulating other interactions between persons involved in morally injurious events.